Present state of evaluating malnutrition in the elderly - analysing indicators - Hrnciarikova, Dana; Juraskova, Bozena; Zadak, Zdenek; Hronek, Miloslav (Biomedical papers, 2006)
Objectives: Malnutrition in old age is a significant problem. The study presents a survey of the basic methods used in the diagnosis of malnutrition in the elderly such as nutritional anamnesis, anthropometrical, laboratory a functional examinations and indicating specific differences as compared with a younger population.Methods: We conducted a search of Czech and foreign literature (using PubMed, Medline) focused on diagnostic methods and examinations of nutritional markers especially by geriatric patients published from 1994 to 2006.Results and conclusions: The examinations we presented are simple, non-invasive methods, which can we use especially for out-patient monitoring of geriatric patients to recognize nutrition disorders. Timely diagnosis of malnutrition in the elderly can prevent patients from worsing self-sufficiency and quality of life of the seniors, increasing the risk of institutionalisation, prolonging hospitalisations due to increased rates of complications and increasing the treatment costs and mortality of geriatric patients.
Keywords: Malnutrition/Geriatric patient/Anthropometry/MNA (mini nutrition assessment)